Overview of respiratory syncytial virus disease in young children - Hoopes JM; Kumar VR (Dove Medical Press, 2012)
J Michael Hoopes1, Veena R Kumar21Medical Information, 2Medical and Scientific Affairs, MedImmune, LLC, Gaithersburg, MD, USAAbstract: Respiratory tract illnesses associated with respiratory syncytial virus (RSV) were first reported more than 160 years ago and gained acceptance as a major respiratory pathogen in the late 1950s. Annual epidemics show a seasonal pattern typically beginning in the late fall and ending in early spring, averaging 5 months in length, and varying in time of onset, offset, and duration depending on geographic location. Manifestations of RSV illness primarily involve the upper respiratory tract but can spread to the lower airways and lead to bronchiolitis and/or pneumonia. Initial infection occurs in approximately two-thirds of children during the first year of life; nearly all children are infected at least once by 2 years of age. Reinfection is common throughout life, but initial illness during infancy generally presents with the most severe symptoms. Medical risk conditions that consistently predispose young children to serious lower respiratory tract infection (LRTI) include congenital heart disease, chronic lung disease, and premature birth. Serious LRTI due to RSV is the leading cause of hospitalization in infants and young children worldwide and annual mean hospital expenses have been estimated to exceed 1 billion dollars in the United States. Young children incur more inpatient and outpatient visits for RSV LRTI than for influenza. RSV has a greater impact than influenza on hospitalization in infants with respect to length of stay, severity/course of disease, and resultant needs for ancillary treatments. Unlike many other childhood illnesses, a vaccine is not currently available for preventing RSV disease.Keywords: bronchopulmonary dysplasia, infants, hospitalization, prematurity, respiratory syncytial virus